Enhancing the Cardiovascular Health Construct With a Psychological Health Metric for Predicting Mortality Risk - Vanessa T. Dinh, MPH; Rahul Hosalli, MPH; Pricila H. Mullachery, PhD, MPH; Brooke Aggarwal, EdD; Charles A. German, MD; Nour Makarem, PhD, MS (JACC: Advances, 2024)
Background: The American Heart Association’s Life’s Essential 8 (LE8) Presidential Advisory deemed psychological health foundational for cardiovascular health (CVH) but did not include it as a CVH metric. Objectives: The purpose of this study was to evaluate associations of a CVH construct enhanced with a ninth metric for psychological health based on readily administered depression screening with mortality risk in U.S. adults. Methods: Participants were 21,183 adults (mean age: 48y, 51% female, 11% Black, 15% Hispanic, 65% White) from the 2011 to 2018 National Health and Nutrition Examination Survey. The LE8 algorithm was used to assess CVH. Two enhanced CVH constructs that include a ninth psychological health metric based on depression screening using the Patient Health Questionnaires (PHQ-2 and PHQ-9) were computed. Multivariable Cox proportional hazards models compared all-cause and cause-specific mortality risk across CVH score tertiles and a priori defined categories (high: 80-100, moderate: 50-79, low: 0-49) in the overall sample and by sex and race and ethnicity. Results: There were 1,397 deaths (414 cardiovascular and 329 cancer deaths). High vs low CVH scores, enhanced with PHQ-2 and PHQ-9, were associated with 69% and 70% lower mortality risk, while a high vs low LE8 score was associated with 65% lower risk (p-trend<0.001). Higher LE8 and enhanced CVH scores predicted lower mortality risk in both sexes and in Black and White but not Hispanic adults and were also associated with lower cardiovascular and cancer mortality. Both enhanced CVH scores had excellent performance for predicting mortality, similar to the LE8 score (C-statistic = 0.843 vs 0.842, P < 0.001). Conclusions: A CVH construct enhanced with psychological health strongly predicts mortality. Inclusion of psychological health as a ninth CVH metric, with depression screening as a feasible proxy in clinical and public health settings, should be considered.